The language of speech and writing - Cornbleet, Sandra; Carter, Ronald, 1947- (London : New York : Routledge, 2001)
Unique in offering students hands-on practical experience of textual analysis focused on speech and writing.
Unit 1. The nature of writing -- unit 2. The nature of speaking -- unit 3. The language of writing -- unit 4. The language of speaking -- unit 5. The relationship between speech and writing -- unit 6. Where boundaries meet.
Includes bibliographical references (pages 127-129) and indexes.
Print version record.
Keywords: English language -- Discourse analysis; English language -- Spoken English; English language -- Written English; English language -- Discourse analysis; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- General; English language -- Discourse analysis; English language -- Spoken English; English language -- Written English; Electronic books